65*65-81*x*x=36*x*x

Simple and best practice solution for 65*65-81*x*x=36*x*x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 65*65-81*x*x=36*x*x equation:


Simplifying
65 * 65 + -81x * x = 36x * x

Multiply 65 * 65
4225 + -81x * x = 36x * x

Multiply x * x
4225 + -81x2 = 36x * x

Multiply x * x
4225 + -81x2 = 36x2

Solving
4225 + -81x2 = 36x2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-36x2' to each side of the equation.
4225 + -81x2 + -36x2 = 36x2 + -36x2

Combine like terms: -81x2 + -36x2 = -117x2
4225 + -117x2 = 36x2 + -36x2

Combine like terms: 36x2 + -36x2 = 0
4225 + -117x2 = 0

Add '-4225' to each side of the equation.
4225 + -4225 + -117x2 = 0 + -4225

Combine like terms: 4225 + -4225 = 0
0 + -117x2 = 0 + -4225
-117x2 = 0 + -4225

Combine like terms: 0 + -4225 = -4225
-117x2 = -4225

Divide each side by '-117'.
x2 = 36.11111111

Simplifying
x2 = 36.11111111

Take the square root of each side:
x = {-6.009252126, 6.009252126}

See similar equations:

| -4/3w=24 | | 12-5/8 | | 3(-x+4)+6=-6x+3 | | 4/x-2=(-4/x+2)+(24/(x-2)(x+2)) | | 14m=400.40 | | 2n+7=5x | | 3v=3.75 | | 2(3x-5)=.5 | | 31.25=x/5 | | -2(x+2)=2x-1+5(2x+1) | | (7-x)(10-x)=(7)(10-1.5x) | | 6/10x=60 | | w/12.8=4 | | .40x+.15(140-x)=.19(140) | | -2(v+9)=7v+45 | | 6i+10y=-13 | | 2x-13=-7(x+7) | | 8x+4=-6+7x | | 3v=9/2 | | .25x+.15(140-x)=.19(140) | | y/4+3.2+5.2 | | 3v+6(v+2)=21 | | 13x=9x+12 | | 7(y-8)+2y=7 | | 30=6/5x | | -6u+3(u+7)=9 | | 3x-2-x=102 | | x(2x-5)+x(2x-2)=(4x+3)(x-2) | | .40x+.15(140-x)=.25(140) | | 2/3(4+3) | | 6x^4+5x^2-6=0 | | 3/8=v+6 |

Equations solver categories